Understanding E-Paper Engagement: The Interplay of Product, Promotion, Culture, and Social Contexts in the Digital News Market - Asiati, Diah Isnaini; Herdiyan (Journal of Management Studies and Development, 2025)
The rapid development of technology has compelled the media industry to shift toward digital-based platforms. Achieving success in this transition requires an effective strategy that considers consumer behavior variables. Given that consumers respond differently to technology, it is essential to identify behavioral factors that have the potential to significantly impact digital media access. This study aims to examine the influence of product and promotional strategies on the decision to purchase e-paper from Bisnis Indonesia, with cultural and social characteristics of consumers as intervening variables. Products and promotions are external stimuli that influence consumer behavior and are shaped by the strength of individual cultural and social contexts. An associative research design was employed to test the hypotheses, involving 155 e-paper subscribers of Bisnis Indonesia from ten representative cities. Primary data were collected through questionnaires, and Structural Equation Modeling (SEM) was used for analysis via LISREL software. The results indicate a positive and significant effect of product and promotional variables on purchasing decisions, which is further strengthened by cultural and social consumer characteristics. Overall, the model explains 89% of the variance in the purchase decision variable.